A generic randomization device for quantitative response variables. Issue 8 (14th September 2017) - Batool, Fatima; Shabbir, Javid
ABSTRACT: We propose a generic randomization device (RD) for the estimation of mean of quantitative sensitive characteristic that make use of additive and multiplicative scrambled responses with blank card strategy. For this generic RD, we work with 12 choices and derive statistical properties of each model and give many immediate results in corollaries. It is interesting to note that various existing models can now be viewed as the special cases of this RD. Finally, various empirical studies have been done for each of these models to evaluate the efficiency performance.